2014 IEEE Wireless Communications and Networking Conference Workshops (WCNCW) 2014
DOI: 10.1109/wcncw.2014.6934881
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm optimization for Mobility Load Balancing SON in LTE networks

Abstract: Abstract-This paper presents a self-optimizing solution for Mobility Load Balancing (MLB). The MLB-SON is performed in two phases. In the first, a MLB controller is designed using Multi-Objective Particle Swarm Optimization (MO-PSO) which incorporates a priori expert knowledge to considerably reduce the search space and optimization time. The dynamicity of the optimization phase is addressed. In the second phase, the controller is pushed into the base stations to implement the MLB SON. The method is applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This would allow load balancing mechanisms to be implemented early, thus resulting in a reduction in latency. A wide range of approaches has been used for load balancing; the reader is referred to a few [70][71][72].…”
Section: Deep Learning-based Mobility Load Balancingmentioning
confidence: 99%
“…This would allow load balancing mechanisms to be implemented early, thus resulting in a reduction in latency. A wide range of approaches has been used for load balancing; the reader is referred to a few [70][71][72].…”
Section: Deep Learning-based Mobility Load Balancingmentioning
confidence: 99%
“…If we denote CIO between a cell and a cell by CIO , , by reducing CIO , , the coverage of a cell is reduced while that of cell increases correspondingly. Various methods are proposed to adjust CIOs between a congested cell and its neighboring cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…From that research also shown that PRB utilization is not a sufficient indicator of cell load for MLB, even in the case of constant bit rate traffic. The method in [5] combines apriori expert knowledge with Multi-Objective Particle Swarm Optimization (MO-PSO), which allows to considerably reduce the search space and the computational time required for executing the MLB algorithm, this paper use offset parameters as its primary MLB consideration variable.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this paper is to give literature contribution in LTE predictive MLB method based on previous research [3][4][5][6][7]. RSRQ is one of LTE measurement parameters that will be analyzed as the primary parameter because its formula ingredients consist of SINR and network load value ( ) , this presented in equation 7.…”
Section: Introductionmentioning
confidence: 99%